Machine learning algorithms and artificial neural networks for predicting schizophrenia using orbital parameters - Emre, Elif; Soylemez, Derya Ozturk; Secgin, Yusuf; Karaagac, Seda Sogukpinar; Kenanoglu, Omer; Aydin, Suleyman (Nature Portfolio, 2025)
A persistent mental illness, schizophrenia has a complicated etiopathogenesis that includes both environmental and genetic elements. This study examined the possibility of diagnosing schizophrenia by utilizing computed tomography (CT) images of the orbit and its structures, which were then examined by artificial neural networks (ANNs) and machine learning (ML) algorithms. A retrospective analysis of the CT scans of 90 healthy people and 90 people with schizophrenia was conducted. Prior to measurement, all CT images underwent preprocessing steps to ensure align-ment and standardization. Height, width, depth, wall length, aperture area, interorbital width, biorbital width, bimalar width, skull transverse diameter, and optic nerve sheath width were among the orbital parameters that were measured. Statistical analysis revealed significant differences between the groups in left orbital width, left orbital aperture area, right optic nerve sheath width, transverse skull diameter, bimalar width, biorbital width, and left medial wall length. ML algorithms and ANNs were applied to the data, with the Extra Tree Classifier (ETC) algorithm achieving the highest accuracy of 0.78 and the Multilayer Perceptron Classifier (MLCP) model of ANN achieving an accuracy of 0.75 after 1000 training iterations. The Random Forest algorithm's SHAP analyzer determined that the left orbital width had the biggest impact on the final outcome. These results add to the expanding field of machine learning applications in psychiatry by indicating that AI-based models that analyze orbital morphometry may be useful instruments for detecting schizophrenia.
Keywords: Schizophrenia; Computed tomography; Machine learning; Artificial neural networks; Orbital parameters